Gestão da informação pessoal realizada em universidade federal: resultado de auditoria baseada em riscos - Albuquerque, Ruth Mayara Guedes de Andrade (2020)
The management of information in public organizations must be directed towards the achievement of organizational objectives, meeting the interests of society and meeting legal requirements. In this sense, for the management of the personal information of public servants, practiced fundamentally within the scope of the organization's people management, the rights of access to information and the inviolability of intimacy must be ensured, observing its general characteristics as public information and its restrictions. Thus, the general objective of this research is to audit, based on risks, the management of personal information carried out at the Personnel Administration Directorate (DAP) of the Federal University of Rio Grande do Norte (UFRN). This objective is operationalized through the following specific objectives: a) to analyze UFRN legislation and legal regulations relevant to the management of personal information; b) to identify the risks associated with the management of personal information in the electronic administrative processes of retirement and pension for death; and c) to propose recommendations that contribute to the improvement of the management of personal information in DAP / UFRN based on risks. To achieve these objectives, an association was made between the intelligence audit method proposed by Carvalho (2010) and the internal governmental audit based on risks. Thus, the proposed study was developed as a research of an applied nature, with a descriptive purpose and qualitative approach, with research-action research as the research strategy, which provides for joint actions between researcher and participants, based on data collection through documentary research, participant observation, interview and focus group. The data were analyzed through content analysis. The systematic examination of the management of the personal information of employees and pensioners, with the objective of evaluating the different laws, the organizational climate, in addition to verifying the good practices adopted and identifying the findings and risks associated with the processes, supported the elaboration of the recommendations that can contribute to improving the management of personal information at DAP / UFRN.